Insights from equitable governance assessments in conservation areas around the world - Naira Dehmel; Kate Schreckenberg; Phil Franks; Nikoleta Jones; Francesca Booker; Cosmas Lambini; Ruth Pinto; Alejandra Cely‐Gómez; Ishmael Chaukura; Donald Chilengwe Chikumbi; Phanith Chou; Ioli Christopoulou; et al. (Conservation Biology, 2026)
Global policy commitments to ensure that protected and conserved areas (PCAs) are equitably governed have increased interest in empirically assessing and analyzing social equity. Although numerous assessments have been conducted in individual PCAs, there is limited empirical insight into equity as a multidimensional concept beyond the site level. We investigated the distributional, procedural, and recognitional equity challenges associated with the governance of PCAs and determined whether the identified challenges differed according to governance type and actor group. We conducted a meta‐level analysis of equitable governance assessments conducted at 37 PCAs in 19 countries that form part of the new SAGE (Site‐level Assessment of Governance and Equity) database. SAGE is a participatory tool for site‐level actors to systematically discuss and assess equity dynamics at their PCAs. We found a large variation in assessment results across the sites. Mitigating the negative impacts of conservation on local communities was most often identified as the biggest challenge. In general, equity assessments tended to be slightly more positive for PCAs governed by and with Indigenous Peoples and local communities than those governed purely by government agencies. Evaluations of different actors often revealed substantial differences in opinion on specific governance issues. In particular, evaluations of PCA decision‐makers tended to be more positive than those of PCA users. As an early‐stage exploration of the growing SAGE database, our findings provide proof of concept that tools for assessing and improving PCA governance gain value from taking multidimensional approaches and need to consider different actors’ views. Although the growing SAGE database holds potential for further insights on how equity is perceived across governance types, ecosystems, and geographical regions, the primary objective of SAGE needs to remain understanding and advancing equity at the site level.

Threats posed to conservation by media misinformation - Adam G. Hart; Rosie Cooney; Amy Dickman; Darragh Hare; Charles Jonga; Paul K. Johnson; Maxi Pia Louis; Rodgers Lubilo; Dilys Roe; Catherine Semcer; Keith Somerville (Conservation Biology, 2020)